Firemen, Barbados. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
The image shows five firemen dressed in full uniform, standing in front of Fire Brigade Station No.2. The fire cart is outfitted with buckets and and what appears to be a hose wounded up on the back wheel. Several of the firemen are holding ropes which are attached to the cart. The building in the background provides an indication of how firehouses were constructed in that era. Back of the postcard : Demerara, March 14.12 - Expect your letter by next mail. Will write you a letter as soon as I receive it. Tell A I haven't heard from him yet. Best, love Alf. The note is addressed to : Miss G. Wetherall, 226 Twickenham Road, Leytonstone, Essex, England. There is a 20 cents British Guiana stamp affixed. This is a divided back postcard.
Landscape; Black & white; 3 1/2 " x 5 1/2 "
Keywords: Architecture; Fire fighters; Buildings; Architectural elements; Fire engines; Uniforms; Bucket brigades; Fires; Fire stations; Firefighting equipment; Firemen; Fire trucks; Fire brigades